Study of Earthquake Damage Potential Based on b-Value Variation in The Special Region of Yogyakarta: Studi Potensi Kerusakan Gempa Bumi Berdasarkan Variasi Nilai B Di Daerah Istimewa Yogyakarta - Wiyono, Wiyono; Budiarta; Herwiningsih, Sri; Nugraha, Aditya Prawira (Sunan Kalijaga Journal of Physics, 2024)
Indonesia is a region prone to various natural disasters, including earthquakes. It is located at the convergence of three major tectonic plates: the Eurasian Plate, the Indo-Australian Plate, and the Pacific Plate. The collision of these three plates causes earthquakes. The Special Region of Yogyakarta is one of the areas that has been impacted multiple times by damaging earthquakes due to its proximity to the meeting point of the Eurasian and Indo-Australian Plates. This study was conducted to examine earthquake statistics in the Special Region of Yogyakarta based on analyses of a-value and b-value in this area, thereby identifying potential earthquake recurrence. Secondary data from the IRIS (Incorporated Research Institutions for Seismology) earthquake catalog from 2006 to 2020 were used for this seismic analysis. The data processing results showed that a-values ranged between 3.5 and 7, with an average value across the entire region of 5.17; meanwhile, b-values ranged between 0.7 and 1.2, with an average value across all areas being 0.775. The area requiring caution is the southern sea region of Special Region Yogyakarta, which has potential for earthquakes with magnitudes up to 6 occurring within intervals of every 5–10 years.